Impact of exposure to malaria and nutritional status on responses to the experimental malaria vaccine ChAd63 MVA ME-TRAP in 5-17 month-old children in Burkina Faso - Morter, Richard; Tiono, Alfred B.; Nébié, Issa; Hague, Oliver; Ouedraogo, Alphonse; Diarra, Amidou; Viebig, Nicola; Hill, Adrian V. S.; Ewer, Katie J.; Sirima, Sodiomon (Frontiers in immunology, 2022)
The experimental malaria vaccine ChAd63 MVA ME-TRAP previously showed protective efficacy against Plasmodium falciparum infection in Phase IIa sporozoite challenge studies in adults in the United Kingdom and in a Phase IIb field efficacy trial in Kenyan adults. However, it failed to demonstrate efficacy in a phase IIb trial in 5-17 month-old children in an area of high malaria transmission in Burkina Faso. This secondary analysis investigated whether exposure to malaria or nutritional status might be associated with reduced responses to vaccination in this cohort. Parasite blood smears and anti-AMA-1 IgG titres were used to assess history of exposure to malaria and weight-for-length Z scores were calculated to assess nutritional status. Differences in vaccine-specific anti-TRAP IgG titre and ex vivo IFNγ ELISpot response were measured between groups. In total, n = 336 volunteers randomised to receive the experimental vaccine regimen were included in this analysis. A positive smear microscopy result was associated with reduced anti-TRAP IgG titre (geometric mean titre: 2775 (uninfected) vs 1968 (infected), p = 0.025), whilst anti-AMA-1 IgG titres were weakly negatively correlated with reduced ex vivo IFNγ ELISpot response (r = -0.18, p = 0.008). Nutritional status was not associated with either humoral or cellular immunogenicity. Vaccine efficacy was also measured separately for vaccinees with positive and negative blood smears. Although not significant in either group compared to controls, vaccine efficacy measured by Cox hazard ratio was higher in uninfected compared to infected individuals (19.8% [p = 0.50] vs 3.3% [p = 0.69]). Overall, this data suggests exposure to malaria may be associated with impaired vaccine immunogenicity. This may have consequences for the testing and eventual deployment of various vaccines, in areas with high endemicity for malaria.Trial RegistrationPactr.org, identifier PACTR201208000404131; ClinicalTrials.gov, identifier NCT01635647.
Online veröffentlicht: 2. Dezember 2022
Gesehen am 31.08.2023